2016
DOI: 10.1111/1540-6229.12137
|View full text |Cite
|
Sign up to set email alerts
|

The Economics of Style: Measuring the Price Effect of Neo‐Traditional Architecture in Housing

Abstract: Vintage effects have received considerable attention from economists in the context of house prices. Although strongly related, the impact of architectural building styles on prices has not been studied yet. Using a cross-sectional hedonic price analysis including building styles of recently developed homes in the Netherlands we find a significant price premium for housing with neotraditional architecture. Extensive intervention by local authorities on the supply side of the housing market seems the most proba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 19 publications
1
14
0
Order By: Relevance
“…This increase reflects human expectations and desires for a city with lots of attractions within walking distance. Buitelaar and Schilder (2017) has shown that there is a price premium of neo-traditional style architecture in housing, although it is not completely clear whether that increase partly stems from a shortage of such properties in the short term, or from their type of quality for that matter. Considering the factors affecting stock prices, it may be the case that the real estate market value is affected by architectural style, though.…”
Section: Research and Discussion: Volatility Of The Housing Market Valuementioning
confidence: 99%
“…This increase reflects human expectations and desires for a city with lots of attractions within walking distance. Buitelaar and Schilder (2017) has shown that there is a price premium of neo-traditional style architecture in housing, although it is not completely clear whether that increase partly stems from a shortage of such properties in the short term, or from their type of quality for that matter. Considering the factors affecting stock prices, it may be the case that the real estate market value is affected by architectural style, though.…”
Section: Research and Discussion: Volatility Of The Housing Market Valuementioning
confidence: 99%
“…Plaut and Uzulena [14] conducted similar research in Riga, Latvia by studying buildings from different time periods. Buitelaar and Schilder [15] looked into architectural styles but included many specific characteristics in their hedonic price model-plot size, construction year, dwelling type, parking type, and land lease conditions, thereby controlling for design value more closely.…”
Section: Valuing Design: a Reviewmentioning
confidence: 99%
“…Homes of this era are valued for their distinct brick architecture. Most studies on housing prices in the Netherlands find the largest premiums for properties built during this era and even for new construction that copied this style (Francke and Van de Minne, 2017b;Buitelaar and Schilder, 2017). Arguably the most expensive neighborhood in Amsterdam, "Zuid" (South), consists of properties only built during the 1920s and 1930s in the Amsterdam school style.…”
Section: Vintages and Submarketsmentioning
confidence: 99%